POTRAIT OF PUBLIC PRIVATE PARTNERSHIP POLICY SUBSTANCES IN REGIONAL HOSPITALS IN INDONESIA - Basabih, Masyitoh (Journal of Indonesian Health Policy and Administration, 2023)
Public Private Partnership (PPP) is a strategy of the Indonesian Government to deal with budget constraints and overcome gaps in infrastructure, access, and quality of health services. PPP on the operational cooperation (KSO) model is the oldest and most widely applied practice by regional hospitals in Indonesia. The implementation of KSO must refer to government policies in the form of laws and regulations. Since its initial implementation until today, the Ministry of Home Affairs, as the body that oversees the local government, has not carried out a comprehensive evaluation of the KSO policy. This study was carried out by conducting document analysis related to the operational cooperation policies of regional hospitals and reviewing the substance of operational cooperation policies at the national and regional levels. Study found that there are no articles governing service level agreements; no performance indicators of cooperation in monitoring and evaluation, limited autonomy; several regional head regulations are not accompanied by technical guidelines; and there are variations in the substance of the regional head regulations. This study concludes that the KSO policy framework for regional hospitals is inadequate, incomplete, and limits the autonomy of regional hospitals.